SETTLEMENT OF CREDITOR BILL DISPUTES IN THE DEBT PAYMENT POSTPONEMENT PROCESS - Adli, Muhammad; Ramlan; Nadirah, Ida (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
There are problems that creditors often have to face in bankruptcy, especially concurrent creditors or ordinary creditors (unsecured creditors), namely to obtain payment of their receivables to debtors who have been declared bankrupt, due to bad faith from the debtor to transfer the assets they own or all efforts by the bankrupt debtor made to hinder the management and settlement of the bankrupt assets (bankruptcy boedel) by the curator. A company, specifically a PT (Limited Liability Company), is unable to pay its debts, and bankruptcy proceedings begin with a creditor filing a petition to the court for past-due bills. Debt restructuring has been the preferred solution for many years to resolve financial problems in a company. Restructuring under a Suspension of Debt Payment Obligations (PKPU) is intended to restructure the debtor's debt payments solely with the goal of restoring the debtor's company to health. Restructuring is more of a rescue measure than a corrective action or permanent fix. One of the legal protections provided by the Bankruptcy Law and PKPU for creditors is the actio paulina, which gives creditors the right to request the cancellation of any legal action not required by the debtor. If a debtor is deemed to have defaulted on a debt repayment agreement with a creditor, they can demand that the agreement be fulfilled, or seek compensation from the defaulting party